PELAKSANAAN PROMOSI OBJEK WISATA ISTANA SIAK PROVINSI RIAU - Siti Aminah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research to purpose is to know how the promotion of the implementation of Istana Siak in Riau Province and to know what response of respondents about implementation of Istana Siak in Riau Province using promotional mix consist of advertising, sales promotion, personal selling and public relation.The sample of this research was taken by accidental sampling. The technique of collecting data in this research used observation, questionaire, and interview. To know the interval range, the writer used likert scale.Based on the result of this research, the respon of respondents about the promotion of the implementation Istana Siak in Rau Province that is advertising, sales promotion, personal selling, and public relation the respon is poorly.keyword : Marketing, Promotion, Advertising, Sales Promotion, Personal Selling,Public Relation, Istana Siak in Riau Province